Professional quality of life in nurses: Contribution for the validation of the Portuguese version of the Professional Quality of Life Scale-5 (ProQOL-5) - Duarte, Joana (2017)
Job stress and burnout are highly prevalent in healthcare professionals, and nurses in particular. Given its deleterious consequences not only for professionals’ well-being but also for patients and organizations, it is important to have adequate measures to assess professional quality of life. This study aimed to offer a contribution for the Portuguese validation of the Professional Quality of Life Scale-5. This scale was designed to measure three dimensions of professional quality of life: compassion satisfaction, burnout, and compassion fatigue. The sample was composed by 390 nurses recruited from five public hospitals from Portugal north and center regions. Participants had on average 38.58 years of age (SD=9.10) and were mainly female, married, and practiced nursing in a variety of fields with an average of 15.66 (SD=9.09) years of practice. Results from the confirmatory factor analysis indicated that the original version of the scale had several problematic items and that a revised version showed superior model fit. In addition, results showed that female scored higher than men on Compassion Satisfaction. Also, nurses working in an oncology hospital had higher scores of Compassion Fatigue. Finally, higher scores of Burnout and Compassion Fatigue, and lower scores of Compassion Satisfaction, were associated with greater Depression, Anxiety, and Stress symptoms. The ProQOL-5 is thus an adequate instrument to assess professional quality of life in nurses and may be valuable for designing effective interventions to tackle burnout and compassion fatigue, and promote satisfaction with one’s work.